2002 a very special year ... (Historia, 2021)
2002 is, from a historical perspective, a very special one. We have hardly reached the halfway mark and already Africa’s first space traveller, Mark Shuttleworth, provides a memorable historical moment. On a more solemn note we take note that in May 2002 the remains of Saartjie Baartman (1789-1816) was returned to South Africa from the distant Europe.1 We are, along with our fellow citizens of Khoisan descent, thankful. 2002 also marks the 400th anniversary of the founding of the Verenigde Oostindische Compagnie. Simultaneously we are made aware of the 350th anniversary of the founding of the company’s refreshment station at the Cape. For many South Africans of European stock it marks a significant event. On 31 May, the first century after the conclusion of the Anglo Boer War (1899-1902), is commemorated. It is this year one decade after the referendum of 1992 during which eligible white voters of South Africa indicated that they were in favour of a multi-racial democratic dispensation. Two years later a constitutional miracle took place at the southern tip of Africa. South Africans have more than enough reason to feel proud of their recent and distant past.
Keywords: historical moment; 2002; Mark Shuttleworth; Saartjie Baartman; Verenigde Oostindische Compagnie; Anglo Boer War